Remembering and Forgetting: Counter-Memories of Tausug Survivors of the 1974 Battle of Jolo (Sulu, Philippines) - Salomon, Elgin Glenn (Al-Jami'ah Research Centre, 2024)
Examining the case of the 1974 Battle of Jolo, this article unpacks how Tausug survivors have constructed, remembered, and made sense of their memories of one of the bloodiest conflicts between the Moro National Liberation Front (MNLF), a Muslim secessionist movement in the southern Philippines, and the Armed Forces of the Philippines (AFP) during the martial law period (1972-1986). As counter-memory to the narratives of the MNLF and the military on the 1974 Battle of Jolo, this study argues that while many of the survivors want to forget and move on from the tragedy of war and violence, their memories revealed layers of problems faced by Muslim Mindanao in the recent decades. Some survivors are eager to document their experiences to reclaim their agency, while many of them transmit their collective memories and life lessons to the next generations of Tausug.[Artikel ini mengungkap bagaimana para orang-orang Tausug, yang mengalami Pertempuran Jolo tahun 1974, membangun, mengingat, dan memaknai ingatan mereka tentang salah satu konflik paling berdarah antara Front Pembebasan Nasional Moro (MNLF) dengan Angkatan Bersenjata Filipina (AFP) selama periode darurat militer (1972-1986) tersebut. Sebagai memori tandingan terhadap narasi MNLF tentang Pertempuran Jolo Tahun 1974, penulis berpendapat bahwa banyak penyintas ingin melupakan dan mengalihkan perhatian mereka dari tragedi perang dan kekerasan di atas. Sementara, konstruksi ingatan mereka mengungkapkan lapisan-lapisan masalah yang dihadapi oleh Muslim Mindanao dalam beberapa dekade terakhir. Beberapa penyintas sangat ingin mendokumentasikan pengalaman mereka untuk mendapatkan kembali hak pilihan mereka, sementara banyak dari mereka tetap meneruskan cerita tentang kenangan kolektif dan pelajaran hidup ini kepada generasi Tausug berikutnya. ]